Pregnancy-Associated Peripartum Cardiomyopathy: Incidence and Clinical Outcomes in Fetomaternal Medicine Department, BMU - Kulsum, Umme; Afroj, Romena; Qumruzzaman, Khondoker; Halim, Tanzila; Zaman, Khondoker Ashab; Jamali, Mohammod Zafor Iqbal (University Heart Journal, 2025)
Background: Peripartum cardiomyopathy (PPCM) is a rare but potentially fatal form of heart failure associated with pregnancy, most commonly presenting in late gestation or the early postpartum period. Limited data are available from low- and middle-income countries regarding its burden and outcomes. This study describes the incidence, clinical characteristics, and in-hospital maternal and neonatal outcomes of PPCM managed at Bangladesh Medical University. Methods: This observational study was conducted in the Department of Fetomaternal Medicine, Bangladesh Medical University (BMU), Dhaka, between January 2023 and January 2024. A total of 35 women diagnosed with PPCM based on echocardiographic evidence of left ventricular systolic dysfunction without prior structural heart disease were included. Demographic variables, clinical presentation, echocardiographic findings, and in-hospital outcomes were analyzed. No post-discharge follow-up was performed. Results: The mean maternal age was 29.1 ± 4.9 years, with 60% multiparous women. PPCM was diagnosed postpartum in 65.7% of cases. Mean left ventricular ejection fraction at diagnosis was 31.2 ± 7.9%. Acute heart failure occurred in 60% of patients, and maternal mortality was 8.6%. Preterm birth and low birth weight were observed in 28.6% and 25.7% of neonates, respectively. Conclusion: Peripartum cardiomyopathy remains a serious obstetric-cardiac condition associated with substantial maternal and neonatal risk. Early recognition and multidisciplinary in-hospital management are essential to improve outcomes in resource-limited settings. University Heart Journal 2025; 21(2): 60-63